Engineering Properties, Treatment Capacity, and Clogging Phenomenon of Adsorbent Pervious Concrete for Stormwater and Wastewater Treatment - Teymouri, Ehsan (Curtin University, 2024)
Adsorbent Pervious Concrete (APC), incorporating industrial wastes and Mineral adsorbents offers a sustainable solution for stormwater and wastewater treatment. Comprehensive experiments, including engineering properties and treatment capacity evaluated APC's effectiveness, revealing optimal mixtures, efficient adsorbents, and clogging phenomena for APC. APC with iron slag and zeolite proved superior for stormwater and wastewater treatment respectively. Clogging affects the removal efficiency and lifetime of APC which was alleviated using the washing-up method.